Book Reviews (Journal of Finance, 1988)
Book reviewed in this article: Equity Markets . By ROBERT A. SCHWARTZ. Money and Capital Markets . By TIM S. CAMPBELL. Short‐Term Financial Management . By NED C. HILL and WILLIAM L. SARTORIS.